Visual Analysis and Interactivity of Board Games as an Innovation in Sequence and Series Learning: A Phenomenological Study of Junior High School Students - Choirudin, Choirudin; Astuti, Puji; Hazarika, Anurag (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
This study aims to analyze in-depth students' experiences using board games specifically designed for learning sequences and series at the junior high school level. This study adopted a phenomenological method to explore students' perceptions, motivations, and interactions during the learning process. The board game not only presents a summary of formulas and practice problems but also emphasizes visual aspects and interactivity as part of the media content integrated into the learning. Data were collected through participant observation, in-depth interviews, and student reflections after the board game learning session. The results showed that the attractive visual design and interactive elements of the board game increased enthusiasm, engagement, and a more meaningful understanding of social arithmetic concepts. Students felt more motivated and active in group discussions and were able to relate mathematics material to real-life situations through play. These findings emphasize the importance of innovative game-based learning media that emphasizes visual aspects and interactivity to create enjoyable and effective learning experiences.